1993
DOI: 10.1111/j.1699-0463.1993.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vitronectin and fibronectin binding by Candida albicans yeast cells

Abstract: Expression of binding to vitronectin (Vn or S‐protein) and fibronectin (Fn) was common among clinical isolates of Candida albicans. Growth at 37°C enhanced expression of both Vn and Fn binding. Some strains expressed higher binding after growth in liquid media and others after growth on solid media. Most strains expressed higher cell surface hydrophobicity after growth on agar media. Vn binding was less influenced by expression of cell surface hydrophobicity than Fn binding. Vn binding to yeast cells was optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…These results suggested that C. albicans isolates possess mechanisms other than biofilm production to establish bloodstream infections. C. albicans is a highly pathogenic Candida species and adhesion may be facilitated by a number of protein receptors on epithelial, endothelial, and foreign body surfaces, including fibronectin (14), fibrinogen (5), and vitronectin (13). Perhaps other virulence factors are more important for the pathogenicity of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that C. albicans isolates possess mechanisms other than biofilm production to establish bloodstream infections. C. albicans is a highly pathogenic Candida species and adhesion may be facilitated by a number of protein receptors on epithelial, endothelial, and foreign body surfaces, including fibronectin (14), fibrinogen (5), and vitronectin (13). Perhaps other virulence factors are more important for the pathogenicity of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…A 37-kDa receptor for laminin that appeared not to recognize other ligands was first detected with an antibody produced to a human highaffinity laminin receptor (30-kDa moiety;Limper and Standing, 1994) and to 13-glucan . Fibronectin inhibited binding of vitronectin to the fungus (Jakab et al, 1993).…”
Section: Removalmentioning
confidence: 96%
“…Serum proteins that bind to the fungus include serum albumin, transferrin, fibrinogen, and the complement C3 fragments, C3d and iC3b (Heidenreich and Dierich, 1985;Bouali et al, 1986;Page and Odds, 1988). ECM components that bind to the fungus include fibronectin, laminin, entactin, collagen type I and type IV, and vitronectin (Skerl et al, 1984;Bouchara et al, 1990;Klotz, 1990;Jakab et al, 1993;Lopez-Ribot and Chaffin, 1994). While the host ligands have been identified, less progress has been made with the identification of the fungal adhesins, many of which appear to be expressed more abundantly on the surfaces of germ tubes than on yeast cells (Heidenreich and Dierich, 1985;Bouali et al, 1986;Bouchara et al, 1990;Lopez-Ribot and Chaffin, 1994).…”
Section: Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which fungal pathogens initiate vascular infections are believed to be complex, and they involve interactions of fungal cells with plasma components, e.g., fibronectin [15], endothelial cells [16] and platelets [17], and avoidance of plasma host defenses, such as complement and phagocytosis. Platelet activation also releases inflammatory mediators, e.g., arachidonic acid metabolites and platelet microbicidal proteins [5,18].…”
mentioning
confidence: 99%